Efficacy of Disinfection of Rigid Endoscope by Ethyl Alcohol 70% - Marco Cesar J. Santos; Henrique F. Pauna; Kazuko U. Graziano; Richard L. Voegels (International Archives of Otorhinolaryngology, 2022)
Introduction Currently, there is no safe, affordable, and ecologically-sustainable guideline that helps prevent contamination through endoscopy. We evaluated the safety of intermediate-level disinfection with 70% ethyl alcohol (w/v) based on biological-load recovery from rigid endoscopes after nasal endoscopy. Objective To demonstrate the efficacy of 70% ethanol in disinfecting rigid endoscopes (REs) to reduce microbial growth in microbiological cultures. Methods After a nasal endoscopy examination, the endoscope was swabbed with gauze; this served as the positive-control sample. The standard operating procedure for intermediate-level disinfection with 70% ethyl alcohol (w/v) following prior cleaning was applied. The endoscope was again swabbed; this served as the experimental sample. The collected material from the endoscope was extracted from gauze pieces, filtered through a 0.22-μm cellulose membrane, and cultivated in different means of culture. Results The results revealed a significant difference between the positive-control and experimental groups regarding the presence of Streptococcus coagulase (-) (p < 0.001), Bacillus spp. (p < 0.001), and Staphylococcus aureus (p = 0.001). These microorganisms were detected in the control group, but not in the experimental group. Conclusions Microorganisms were not recovered from the samples of the experimental group, demonstrating the efficacy and the germicidal action of 70% ethyl alcohol (w/v) as a means of achieving intermediate-level disinfection.